Beyond its preferential niche: Brucella abortus RNA down-modulates the IFN-γ-induced MHC-I expression in epithelial and endothelial cells - Serafino, Agustina (2024)
Fil: Serafino, Agustina. Instituto de Medicina Experimental-Consejo Nacional de Investigaciones Científicas y Técnicas, Academia Nacional de Medicina; Buenos Aires, Argentina